Use of Design Sprint in PBL Modules– A Longitudinal Case Study Approach (Global Journal of Computer Science and Technology, 2023)
Project Based Learning PBL modules have become an inevitable part in SE curriculums Industry relevance of PBL mechanisms have further strengthened this crucial need Design Sprint is well known as a PBL approach which enhances transferable skills in students Design Sprint is also a widely used mechanism in software industry projects Therefore Design Sprint could be used to enhance the outcomes of SE undergraduate PBL projects This study makes use of a longitudinal case study approach to investigate the effectiveness of using Design Sprint approach in a SE undergraduate module which used PBL The study focusses a group of students 111 and academics 12 in SE degree program in a private higher education institute in Sri Lanka Qualitative data gathered from the target audience in two distinctive occasions to investigate the effectiveness of Design Sprint in PBL projects
Keywords: design sprint; PBL; SE